Comparison of Thermal Seed Treatments to Control Snow Mold in Wheat and Loose Smut of Barley - Bänziger, Irene; Kägi, Andreas; Vogelgsang, Susanne; Klaus, Seraina; Hebeisen, Thomas; Büttner-Mainik, Annette; Sullam, Karen E. (Frontiers in Agronomy, 2022)
Due to increasing demands to reduce chemical plant protection products, including prophylactic chemical seed treatments, there is a renewed interest in thermal seed treatments for cereal crops. We carried out contemporary evaluations of various alternative seed treatments for economically relevant cereal diseases in Switzerland. Thermal seed treatments were evaluated for effectiveness against two seed-borne diseases commonly found in Swiss cereal production, snow mold (Microdochium majus) and loose smut of barley (Ustilago nuda). Field trials testing seed treatments against M. majus on wheat were conducted across four growing seasons from 2016/17 to 2019/20 and against U. nuda on barley across three growing seasons from 2016/17 to 2018/19. The focus was primarily on thermal seed treatments, including steam, hot air, and warm water. Additionally, Cerall®, based on the microorganism Pseudomonas chlororaphis strain MA 342, was included in two of the trials focusing on M. majus. Steam, warm water, and hot air showed high efficacy against M. majus, while Cerall® showed no disease reduction. In the M. majus 2018/19 trial, a combination of poor field conditions, a weak seed lot and high disease pressure reduced seed germination. The 2019/20 M. majus field trial, which occurred in improved field conditions and included both the same seed lot from 2018/19 and a second, stronger and less diseased lot, showed an improved efficacy of the steam treatments. The warm water treatments were found to be the only effective thermal treatment against U. nuda. Our results demonstrate that the steam treatments more readily affected germination rate in a highly diseased seed lot, while warm water treatments showed limited damage to the seed. Warm water was found to be the most effective thermal treatment against both diseases, and constraints in implementing such a treatment are discussed. If the steam treatment parameters are correctly set to minimize damage to the plant, it offers effective protection against certain seed borne diseases. Overall, the results from this study give more information about effectiveness of alternative seed treatments under various field conditions.